2016
DOI: 10.1002/met.1600
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating global reanalysis precipitation datasets with rain gauge measurements in the Sudano‐Sahel region: case study of the Logone catchment, Lake Chad Basin

Abstract: Africa has a paucity of long term reliable meteorological ground station data and reanalysis products are used to provide the climate estimations that are important for climate change projections. In this paper monthly observed precipitation records in the Logone catchment of the Lake Chad Basin are used to evaluate the performance of two global reanalysis products: the Climate Forecasting System Reanalysis (CFSR) and ERA Interim datasets. The two reanalysis products reproduced the monthly, annual and decadal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…This follows the finding of Nkiaka et al [21] who showed that CFSR and ERA-Interim precipitation estimates could replicate the seasonal cycle of rainfall in the catchment. However, from the streamflow hydrographs shown in Figures 3-6 it can be observed that WFDEI and CFSR were able to simulate low flows (baseflow) throughout the period under study while ERA-Interim overestimated low flows in most years during the same period.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…This follows the finding of Nkiaka et al [21] who showed that CFSR and ERA-Interim precipitation estimates could replicate the seasonal cycle of rainfall in the catchment. However, from the streamflow hydrographs shown in Figures 3-6 it can be observed that WFDEI and CFSR were able to simulate low flows (baseflow) throughout the period under study while ERA-Interim overestimated low flows in most years during the same period.…”
Section: Resultssupporting
confidence: 72%
“…This suggest that rainfall input plays a significant role in model calibration because it has the potential to influence calibrated parameters as reported by [29]. Nevertheless, the significant variability in CFSR and ERA-Interim datasets in this study follow the findings of [21] in the Logone catchment.…”
Section: Model Evaluationsupporting
confidence: 49%
See 1 more Smart Citation
“…Although this issue may be resolved by using satellite or reanalysis data sets, these too also need to be validated against in situ rain gauge measurements (e.g. Nkiaka et al ., 2016a). Accuracy, of satellite and reanalysis rainfall forecast models thus depends on the quality of gauge data used for calibration and are inevitably affected by the sparsity of gauge data or temporally incomplete gauge time series in the region under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nkiaka et al . () found that there are good correlations between ERA‐Interim and rain gauge datasets over the Lake Chad Basin, such that the bias and mean absolute error of ERA‐Interim were found on average 2% and 6.5 mm month −1 , respectively.…”
Section: Model Description and Methodologymentioning
confidence: 99%